2019
DOI: 10.15366/rimcafd2019.74.005
|View full text |Cite
|
Sign up to set email alerts
|

Motivación en La Práctica Del Judo en Deportistas No Profesionales

Abstract: El presente estudio tiene como objetivo determinar y analizar las relaciones y diferencias existentes entre el clima motivacional, en base al nivel competitivo en judocas no profesionales. Participaron un total de 121 judocas chilenos no profesionales (70 hombres y 51 mujeres) con edades comprendidas entre los 18 y 40 años, provenientes de siete clubes de judo. Completaron una hoja de autoregistro de variables sociodemográficas y un cuestionario de clima motivacional (PMCSQ-2). Los resultados indican que en lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
6
0
2
Order By: Relevance
“…In this study, we found slightly higher mean values among men in the dimensions measured by the PSQ [26] (d = −0.44). Studies carried out by various authors [53][54][55][56] obtained similar results to those deduced in this work, as their figures were lower for women in perceived physical condition due to the difference in habits between both genders. Students with higher physical self-concept have a better perception of their own health and take care of their eating and resting habits [57].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we found slightly higher mean values among men in the dimensions measured by the PSQ [26] (d = −0.44). Studies carried out by various authors [53][54][55][56] obtained similar results to those deduced in this work, as their figures were lower for women in perceived physical condition due to the difference in habits between both genders. Students with higher physical self-concept have a better perception of their own health and take care of their eating and resting habits [57].…”
Section: Discussionsupporting
confidence: 88%
“…On the contrary, high scores in ego involvement are associated with low scores in cohesion, a circumstance favored by the sociomotor space where the technical exercise in AGG takes place, limited in a small (13 × 13 m) and closed area, endorsed by previous studies Quested and Duda (2009), Iglesias et al (2019). This aspect was highlighted in previous research, where basketball, volleyball, and handball are more socially cohesive than sports that take place in a large area such as rugby and football (Rusu (2020), as well as in Castro-Sánchez et al (2019b) with judocas.…”
Section: Discussionmentioning
confidence: 82%
“…However, in the case of the association between Autonomy and Social Relations with the peer group, the association is negative because people who enjoy great autonomy usually appreciate the time they spend alone, which does not mean that they are less social people. However, when a person enjoys their time alone, they usually dedicate less time to social relations, which could explain the association [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%